Analyzing social media networks with NodeXL : insights from a connected world - Hansen, Derek L.; Schneiderman, Ben; Smith, Marc A. (Morgan Kaufmann, 2011)
Analyzing Social Media Networks with NodeXL offers backgrounds in information studies, computer science, and sociology. This book is divided into three parts: analyzing social media, NodeXL tutorial, and social-media network analysis case studies. Part I provides background in the history and concepts of social media and social networks. Also included here is social network analysis, which flows from measuring, to mapping, and modeling collections of connections. The next part focuses on the detailed operation of the free and open-source NodeXL extension of Microsoft Excel, which is used in all exercises throughout this book. In the final part, each chapter presents one form of social media, such as e-mail, Twitter, Facebook, Flickr, and Youtube. In addition, there are descriptions of each system, the nature of networks when people interact, and types of analysis for identifying people, documents, groups, and events. *Walks you through NodeXL, while explaining the theory and development behind each step, providing takeaways that can apply to any SNA *Demonstrates how visual analytics research can be applied to SNA tools for the mass market *Includes case studies from researchers who use NodeXL on popular networks like email, Facebook, Twitter, and wikis *Download companion materials and resources at https://nodexl.codeplex.com/documentation